Co-authorship Status of the Journal of Family Research of Shahid Beheshti University - Hossein Moradimoghadam; Rahman Marefat; Abdolazim Volooei (مجله علم‌سنجی کاسپین, 2018)
Background and aim: Scientific collaboration is a process in which two or more authors share their resources and talents in order to create a common work. The aim of this study was to investigate the co-authorship status of the Journal of Family Research of Shahid Beheshti University. Material and methods: The scientometric methods were used in the current study. The population included all articles from the Journal of Family Research of Shahid Beheshti University from 2005 to 2016. Totally, 320 articles and 911 authors were investigated, and the data were analyzed using Excel and SPSS. Findings: The findings of the study showed that each article of this Journal had 2.8% authors in the period of the study. It was also found that the average co-authorship rate in articles of the Journal of Family Research was 0.60% during these years. Moreover, the highest number of authors in the articles was allocated to the universities of Shahid Beheshti, Isfahan and Tehran, respectively. In total, the average number of authors in the articles of the Journal of Family Research was three. Conclusion: The scientific co-authorship rate was low in the Journal of Family Research.